Transvaginal NOTES hysterectomy with the Chinese robotic single port platform - Report of two cases - Chunhua Zhang; Qing Li; Fang Fang; Shanchuang Wei; Qian Lu; Xiaoming Guan (Intelligent Surgery)
Objective: To demonstrate the surgical techniques employed in the robotic single port (SP) transvaginal natural orifice transluminal endoscopic surgery (RSP-vNOTES) for hysterectomy utilizing a domestically developed robotic system in China. Methods: We performed two cases of RSP-vNOTES hysterectomy for patients presenting with persistent vaginal bleeding resulting in atypical endometrial hyperplasia per endometrial biopsy. Procedures were initiated with traditional TVH and seamlessly transitioned to the robotic platform when necessary to complete the entire process. The robotic docking process was executed smoothly. Two elbowed instruments, a bipolar grasper, a pair of monopolar scissors, and a facing-upward camera were used. The hysterectomies were carried out precisely, without complications. Bilateral salpingo-oophorectomy was performed in the first patient and bilateral salpingectomy in the second. The vaginal cuff was closed continuously through a transvaginal approach after undocking. Results: Both patients were discharged on the third postoperative day, with satisfactory surgical results and no complications. Conclusions: The domestically developed Chinese Robotic SP system demonstrates feasibility for RSP-vNOTES procedures of hysterectomy. This approach amalgamates the advantages of both vaginal and robotic surgeries, incorporating surgical triangulation with an elbowed function that simplifies surgical manipulation. However, further studies with larger sample sizes and potential comparative analyses are essential to validate the merits and safety of adopting this platform.